2021
DOI: 10.1038/s41598-020-80804-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the protective effects of resveratrol, curcumin and sulforaphane against LPS/IFN-γ-mediated inflammation in doxorubicin-treated macrophages

Abstract: Doxorubicin (DOX) chemotherapy is associated with the release of inflammatory cytokines from macrophages. This has been suggested to be, in part, due to DOX-mediated leakage of endotoxins from gut microflora, which activate Toll-like receptor 4 (TLR4) signaling in macrophages, causing severe inflammation. However, the direct function of DOX on macrophages is still unknown. In the present study, we tested the hypothesis that DOX alone is incapable of stimulating inflammatory response in macrophages. Then, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 57 publications
1
34
1
Order By: Relevance
“…49 Previous studies have shown that the disruption of the intestinal barrier causes the leakage of endotoxin into the circulation, where it binds to the TLR4 receptor and activates the NF-κB pathway, which in turn induces the production of inflammatory cytokines and induces systemic inflammation. 50 Occludin was the first identified tight junction specific integral membrane protein. 51 The extracellular portion and transmembrane domain of Occludin regulate paracellular permeability, and the intracellular portion is linked to the actin cytoskeleton by ZO-1.…”
Section: Discussionmentioning
confidence: 99%
“…49 Previous studies have shown that the disruption of the intestinal barrier causes the leakage of endotoxin into the circulation, where it binds to the TLR4 receptor and activates the NF-κB pathway, which in turn induces the production of inflammatory cytokines and induces systemic inflammation. 50 Occludin was the first identified tight junction specific integral membrane protein. 51 The extracellular portion and transmembrane domain of Occludin regulate paracellular permeability, and the intracellular portion is linked to the actin cytoskeleton by ZO-1.…”
Section: Discussionmentioning
confidence: 99%
“…CA regulates the above effects by inhibiting pro-inflammatory cytokine production and reducing inflammation [ 42 ]. CA and histidine supplementation via drinking water and diet protected diabetic Balb/cA mice by significantly suppressing pro-inflammatory cytokines, such as IL-6 and TNF-α, and inhibiting diabetes-induced neuropathy [ 43 ]. CA has recently been shown to suppress and slow aging in cultured human fibroblasts [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of doxorubicin on macrophages have been reported (Chen et al, 2023, Saleh et al, 2021). To test the hypothesis that these cells were implicated in the inflammatory phenotype of mice treated with doxorubicin, we treated bone marrow-derived macrophages (BMMs) with this drug for 16 hours.…”
Section: Resultsmentioning
confidence: 99%